[New Zealand album] - Morris, J., photographer (1900)
Rural and city scenes in Dunedin, Christchurch, Nelson, Auckland, Lake Taupo; goldmines; Maoris. Many are signed Morris or J.M.
Keywords: New Zealand -- Pictorial works